Development and evaluation of the electromagnetic hypersensitivity questionnaire. - Eltiti, S; Wallace, D; Zougkou, K; Russo, R; Joseph, S; Rasor, P; Fox, E (2007)
Electromagnetic hypersensitivity (EHS) syndrome is usually defined as a condition where an individual experiences adverse health effects that he or she believes is due to exposure to objects that emit electromagnetic fields. The aim of this study was to develop a questionnaire that would identify the key symptoms associated with EHS and determine how often these symptoms occur in the general population of the United Kingdom. In the pilot study, an EHS questionnaire was developed and tested. In Study 1 the EHS questionnaire was revised and sent to a randomly selected sample of 20,000 people. Principal components analysis of the symptoms resulted in eight subscales: neurovegetative, skin, auditory, headache, cardiorespiratory, cold related, locomotor, and allergy related symptoms. Study 2 established the validity of the questionnaire in that EHS individuals showed a higher severity of symptoms on all subscales compared to the control group. The two key results of this study were the development of a scale that provides an index of the type and intensity of symptoms commonly experienced by people believing themselves to be EHS and a screening tool that researchers can use to pre-select the most sensitive individuals to take part in their research.